2006
DOI: 10.1590/s1415-47572006000100009
|View full text |Cite
|
Sign up to set email alerts
|

Elastin (ELN) gene point mutation in patients with inguinal hernia

Abstract: Groin hernias emerge at the myopectineal orifice of Fruchaud which is closed off by the fascia transversalis. Our previous studies showed structural and quantitative changes of the fascia transversalis elastic fibers of inguinal hernia patients and elderly people. The present study used single-strand conformation polymorphism (SSCP) elastin (analysis to investigate the 34 exons of the ELN gene of 49 inguinal hernia patients (7 females, 42 males aged 58.7 ± 19.82 years) and 75 non-herniated controls (35 females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
2
7
0
1
Order By: Relevance
“…40 One mutation of the ELN gene is significantly associated with inguinal hernia in humans. 13 The ZFPM2 gene had a significant association with hernias via family-based analyses as well as case control analysis in the present study. Two reports indicate that ZFPM2 is required in the normal development of lung and may be important in the progression of diaphragmatic hernias in mice and humans.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…40 One mutation of the ELN gene is significantly associated with inguinal hernia in humans. 13 The ZFPM2 gene had a significant association with hernias via family-based analyses as well as case control analysis in the present study. Two reports indicate that ZFPM2 is required in the normal development of lung and may be important in the progression of diaphragmatic hernias in mice and humans.…”
Section: Discussionsupporting
confidence: 53%
“…A decrease of type I collagen, increase in type III collagen, or both, have been found in humans with recurrent hernias, which suggests that the relative composition of collagen types determines the elastic properties of tissue. 10 Furthermore, MMP2, HOXA10 and elastin (ELN) genes have been found to be related to the collagen metabolism process in humans, [11][12][13] and COL2A1 is located in one identified pig inguinal hernia associated QTL region on SSC5 (90 cM). 9 Therefore, 6 genes including collagen type I α 1 (COL1A1), collagen type I α 2 (COL1A2), COL2A1, MMP2, HOXA10 and ELN were also chosen for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also been conducted to define the mutations in the elastin gene in patients with no chromosomal syndromes. Rodrigues et al [27] proved the assumption that the ELNf (elastin isoform f precursor) gene exon 20 g28197A > G missense mutation triggers the construction of irregular elastic fibers and the forfeiture of fascia transversalis utility and therefore is involved in the genesis of IH. Rodrigues Junior et al [8] showed elevated quantities of elaunin and oxytalan elastic fibers in TF from DIH patients compared to IIH patients in another study.…”
Section: Connective Tissue-related Molecular Mechanisms For Ihmentioning
confidence: 99%
“…Significantly lower amounts of collagen and higher amounts of elastic fibers in transversalis fascia are observed in patients with direct inguinal hernia than those with indirect inguinal hernia (Pans et al, 2001;Rodrigues et al, 2002). A point mutation (28197A>G) in the elastin (ELN) gene leads to an S422G amino acid substitution in the elastin hydrophobic domain, it shows a statistically significant association with inguinal hernia (Rodrigues et al, 2006), possibly due to abnormal elastic fiber and impaired fascia transversalis function. A marked reduction of the collagen I/Ш ratio respective in the fascia transversalis, hernial sac and skin of individuals with inguinal hernias compared with controls was demonstrated by immunohistochemistry and Western Blot analysis (Klinge et al, 1999a(Klinge et al, , 1999b(Klinge et al, and 1999c.…”
Section: Collagen Hypothesismentioning
confidence: 99%